{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

solution AS2

# solution AS2 - 1-f x = 3 vii lim x → 1 f x = 3 viii lim x...

This preview shows pages 1–6. Sign up to view the full content.

Page 1 Math151 Assignment 2 - Section 2.2

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Page 1 Math151 Assignment 2 - Section 2.3
Page 1 Math151 Assignment 2 - Section 2.4

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Assignment 2 Solutions Instructor’s Questions: 1. Let f ( x ) = 2 x | x | if x < - 2 - 1 if x = - 2 4 - x 2 if - 2 < x < 1 2 if x = 1 2 x + 1 if x > 1 (a) Sketch a graph of f . (b) Find f ( - 3), f ( - 2), f (0), f (1) and f (5). (c) Find the following limits, if they exist: i. lim x →-∞ f ( x ) ii. lim x →- 3 f ( x ) iii. lim x →- 2 - f ( x ) iv. lim x →- 2 + f ( x ) v. lim x →- 2 f ( x ) vi. lim x 1 - f ( x ) vii. lim x 1 + f ( x ) viii. lim x 1 f ( x ) ix. lim x →∞ f ( x ) 1
Solution: Figure 1: Problem 1 (a) (b) f ( - 3) = - 2, f ( - 2) = - 1, f (0) = 4, f (1) = 2, and f (5) = 9. (c) Find the following limits, if they exist: i. lim x →-∞ f ( x ) = - 2 ii. lim x →- 3 f ( x ) = - 2 iii. lim x →- 2 - f ( x ) = - 2 iv. lim x →- 2 + f ( x ) = 0 v. lim x →- 2 f ( x ) Does not exist since the right-hand and the left- hand limits at x = - 2 are not equal. vi. lim x

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 1-f ( x ) = 3 vii. lim x → 1 + f ( x ) = 3 viii. lim x → 1 f ( x ) = 3 ix. lim x →∞ f ( x ) = ∞ (This is more precise than ”The limit does not exist”, even the statement is true.) 2 2. Find constants a and b such that lim x → √ ax + b-2 x = 1 . Solution. Since the denominator is approaching 0, for this limit to exist the numerator must also approach 0. Thus 0 = lim x → ( √ ax + b-2) = √ b-2 ⇒ √ b = 2 ⇒ b = 4 . Next 1 = lim x → √ ax + 4-2 x = lim x → √ ax + 4-2 x · √ ax + 4 + 2 √ ax + 4 + 2 = lim x → ax x ( √ ax + 4 + 2) = lim x → a √ ax + 4 + 2 = a 4 Thus a = 4. 3...
View Full Document

{[ snackBarMessage ]}

### Page1 / 6

solution AS2 - 1-f x = 3 vii lim x → 1 f x = 3 viii lim x...

This preview shows document pages 1 - 6. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online